Legal Cancellation of Property Rights Certificate to Land which is Enough with Insurance Rights - Aqsa Januar Widi Kurnianda (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
If observed, the provisions of Article 32 paragraph (1) of the PP on Land Registration have weaknesses, where the state does not guarantee the truth of the physical data and juridical data presented and there is no guarantee for the certificate owner because at any time they will get a lawsuit from other parties who feel aggrieved over issuance of certificate. And if it turns out that in the future the land rights are disputed and the mortgage giver is declared not as the person / party entitled to the land, which will thus have implications for the mortgage that burdens the land rights. This study aims to find out the legal consequences of canceling a certificate of ownership of land that is being encumbered by Mortgage at the Land Office of Palembang City and to find out the legal protection for separate creditors as holders of Mortgage on the canceled land title certificate. The approach method used in writing this law is sociological juridical which means carried out with observation steps carried out in accordance with the formulation of the problem, collecting data from literature or doctrinal research from secondary materials and interviews and to find out the problems being researched which in this case relates to the object. study. The research problem is analyzed with the theory of authority, the theory of legal certainty, and the theory of legal protection. The results of the study indicate that the legal consequences of canceling the certificate of ownership of land that are being encumbered with Mortgage Rights, namely the change in the position of the creditor, which was originally located as a preferred creditor which has material rights, then is located as a concurrent creditor who has individual rights. Legal protection for creditors for the abolition of the object of mortgage can be obtained with preventive legal protection and repressive legal protection. Preventive legal protection is legal protection that is preventive in nature, that is, it can be through an agreement by including a clause regarding the replacement of the dependent object with other objects owned by the debtor in the event of the elimination of the right to the dependent object that is burdened with the mortgage.